2017
DOI: 10.1590/s1984-29612017010
|View full text |Cite
|
Sign up to set email alerts
|

New morphological data and molecular diagnostic of Henneguya friderici (Myxozoa: Myxobolidae), a parasite of Leporinus friderici (Osteichthyes: Anostomidae) from southeastern Brazil

Abstract: The myxozoan Henneguya friderici is a parasite of the gills, intestine, kidney and liver of Leporinus friderici, a characiform fish belonging to the family Anostomidae. Forty-two specimens of L. friderici that had been caught in the Mogi Guaçú River, state of São Paulo, were studied. Elongated white plasmodia were found in the gill filaments of 10 host specimens (24%). The mature spores had an ellipsoidal body with polar capsules of equal size and caudal length greater than body length. This study also describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Parasites of the genus Henneguya are considered one of the most abundant parasites affecting larval fish stages, either in the wild or under farmed conditions (Naldoni et al, 2011;Vidal & Luque, 2017), with more than 200 described species (Dyková & Lom, 1992;Lom & Dyková, 2006). In Brazil, 40 species of Henneguya sp.…”
Section: ___________________ Corresponding Editor: Jesús Ponce-palafoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites of the genus Henneguya are considered one of the most abundant parasites affecting larval fish stages, either in the wild or under farmed conditions (Naldoni et al, 2011;Vidal & Luque, 2017), with more than 200 described species (Dyková & Lom, 1992;Lom & Dyková, 2006). In Brazil, 40 species of Henneguya sp.…”
Section: ___________________ Corresponding Editor: Jesús Ponce-palafoxmentioning
confidence: 99%
“…In Brazil, 40 species of Henneguya sp. (Cnidaria: Myxosporea: Myxobolidae) were described infecting a large variety of commercial fishes (Eiras et al, 2008;Naldoni et al, 2011;Vidal & Luque, 2017). Infection due to Henneguya species occurs mainly in the gill arches, which leads to destruction of the gill filaments, causing respiratory failure (Dyková & Lom, 1992;Velasco et al, 2015), but it can also be observed to be parasitizing kidney of freshwater fish Piaractus mesopotamicus, causing several histological alterations (Manrique et al, 2017).…”
Section: ___________________ Corresponding Editor: Jesús Ponce-palafoxmentioning
confidence: 99%